Introduction: Learning to be Muslim in West Africa. Islamic Engagements with Diversity and Difference - Nolte, Insa (Islamic Africa, 2019)
In West Africa, Muslim learning has historically been shaped by two key engagements: the participation in wider Islamic debates and the co-existence with non-Muslims. In the twentieth and twenty-first century, Islamic education in West Africa was transformed by the imposition of the secular state and Western education. But as Muslims encountered secularism and Christianity, they also increasingly drew on pedagogies that emanated from Middle Eastern and Asian Islam. The articles in this Special Issue illustrate that as Islamic scholars and leaders from different backgrounds engaged simultaneously with the diversity of global Islam and the growing presence of secular and Christian institutions, they developed a multiplicity of educational practices and visions. Thus learning to be Muslim in West Africa reflects both the engagement with Islamic discourse and debates about the boundaries of Islam.